A novel high sensitive capacitive pressure sensor for measuring intraocular pressure - Mardaneh, Sajjad; Taghi Dokht Ahrabi, Maryam; Yousef Shafiei, Seyyed (International Journal of Engineering and Technology, 2019)
In this paper, a new MEMS-based capacitive pressure sensor have been designed and characterized to measure pressures in the range of 0 - 60 mmHg (i.e. 0-8 KPa) that is in the range of intraocular pressure sensors. Intraocular pressure sensors are important in the early detection and treatment of Glaucoma which is an incurable disease. Two sensor designs incorporating conventional and slotted diaphragm are implemented and compared to realize the pressure-sensitive components. The novelty of this method relies on diaphragm includes some slots to reduce the effect of residual stress and stiffness of diaphragm and increase sensor sensitivity. The slotted diaphragm makes ca-pacitive pressure sensor more sensitive, that is more suitable for measuring intraocular pressure sensor. The results yield a sensitivity of 1.113×10-4 1/Pa for the conventional and 2.375×10-4 1/Pa for the slotted pressure sensor with a 0.5 × 0.5 mm2 diaphragm. It can be seen that the sensitivity of the sensor with slotted diaphragm increased 2.13 times compared with the conventional diaphragm. Furthermore, the resonance frequency for the conventional diaphragm is 143.29 KHz while the resonance frequency for the slotted diaphragm is 128.75 KHz.
Keywords: Capacitive Pressure Sensor; COMSOL Multiphysics; Deflection; Displacement; Intraocular Pressure Sensor; MEMS.